2022
DOI: 10.1177/23800844221088833
|View full text |Cite
|
Sign up to set email alerts
|

Dental Extractions under General Anesthesia: New Insights from Process Mining

Abstract: Introduction: Tooth extraction under general anesthetic (GA) is a global health problem. It is expensive, high risk, and resource intensive, and its prevalence and burden should be reduced where possible. Recent innovation in data analysis techniques now makes it possible to assess the impact of GA policy decisions on public health outcomes. This article describes results from one such technique called process mining, which was applied to dental electronic health record (EHR) data. Treatment pathways preceding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Dental treatment under GA is considered expensive and resource-intensive, which places a considerable financial burden on the National Health Service (NHS) in the UK and other countries [3,13]. For example, it was reported that about 43,700 children aged ≤16 years were admitted to hospitals in England in 2015-2016 for the extraction of multiple teeth under GA, which cost GDP 30 million [3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Dental treatment under GA is considered expensive and resource-intensive, which places a considerable financial burden on the National Health Service (NHS) in the UK and other countries [3,13]. For example, it was reported that about 43,700 children aged ≤16 years were admitted to hospitals in England in 2015-2016 for the extraction of multiple teeth under GA, which cost GDP 30 million [3].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was reported that about 43,700 children aged ≤16 years were admitted to hospitals in England in 2015-2016 for the extraction of multiple teeth under GA, which cost GDP 30 million [3]. In 2018-2019, 44,685 surgical procedures were carried out in English hospitals to remove more than one tooth in children aged 18 years and under, which cost GDP 41.5 million [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations